Development of Nutrant Application Based on Android Platform for Individual Nutrition Assessment - Al Rahmad, Agus Hendra; Iskandar, Iskandar; Hafid, Fahmi (JURNAL INFO KESEHATAN, 2024)
The nutritionist should keep abreast of technological developments to improve information on nutritional needs and assessment of individual nutritional status, supporting efficient community and clinical nutrition reporting, which can facilitate nutrition assessment and intake monitoring. This study aims to develop and evaluate the functionality and usability of an Android-based nutrition assessment application, NutrAnt, for individual nutrition assessment. The design used a Research and Development (R&D) model conducted in Banda Aceh City and Aceh Besar from April - December 2023. The subjects involved 53 nutritionists and nutrition experts who were purposively selected. The method used is the Waterfall Models which consists of four stages: problem identification, system design, system development, and system testing. Application testing is done with blackbox testing and usability testing. Results showed high functionality ratings, with an 85.5% satisfaction score from Health Office nutritionists and a 90.0% score from a team of nutrition experts. NutrAnt proves to be a valuable tool, significantly enhancing the capabilities of nutritionists in assessing patient nutritional needs both in community and clinic settings. Future development should consider expanding the app's functionalities and adapting it for a broader user base. This innovation offers a practical advancement in digital tools for nutrition assessment, with promising implications for improved nutritional care and reporting.